Cultivating Religious Tolerance in Indonesia: An Orientational Pluralism of Barasuara’s Hagia - Anadza, Hirshi; Pasopati, Rommel Utungga; Syarifuddin, Syarifuddin; Zaimudin, Ashlaha Baladina (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2023)
This article examines how Barasuara's composition "Hagia" contributes to promoting religious tolerance and orientational pluralism in Indonesia, aiming to comprehend the manifestation of these concepts within the musical piece. The study uses qualitative methods and Heim's theoretical frameworks to show that the lyrics of "Hagia" show a diverse and pluralistic ethos by focusing on a number of different points of view and themes that help create an environment where religious tolerance can thrive. The study results indicate that cultivating a pluralistic understanding through music can foster acceptance and inclusivity among individuals of different religious backgrounds. Furthermore, the article argues that the influence of religion may vary between younger and older individuals. "Hagia" transcends relativism by advocating for active consideration and recognition of others' beliefs, thereby suggesting that a pluralistic understanding can aid individuals in becoming more accepting and inclusive of their religion as well as others, or what can be called religious tolerance. This study contributes to a more nuanced comprehension of societal responsibilities in fostering a more inclusive and tolerant society. It facilitates a more comprehensive understanding of the subject matter at hand.